2016
DOI: 10.1007/s00586-016-4807-7
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for parameters of sagittal spinal alignment in healthy subjects: an analysis of gender specific differences and changes with aging in 626 asymptomatic individuals

Abstract: Standard values of spino-pelvic sagittal alignment were established in each gender and each decade from 20' to 70'. A remarkable change of spino-pelvic sagittal alignment was seen from 7th decade to 8th decade in asymptomatic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
67
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 22 publications
14
67
3
Order By: Relevance
“…In this study, we did not directly control for pelvic tilt by placing a pillow underneath the legs in supine. Despite this, our measured Cobb angles in standing are consistent with a prior report that also included young, asymptomatic individuals (48). Further, it has been shown that externally applied loads during standing can alter the lumbar spine to be in less lordosis in pMRI (6, 36, 37).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we did not directly control for pelvic tilt by placing a pillow underneath the legs in supine. Despite this, our measured Cobb angles in standing are consistent with a prior report that also included young, asymptomatic individuals (48). Further, it has been shown that externally applied loads during standing can alter the lumbar spine to be in less lordosis in pMRI (6, 36, 37).…”
Section: Discussionsupporting
confidence: 91%
“…Defined as the angle subtended from a line running from the bicoxofemoral axis to the midpoint of the sacral endplate and a line perpendicular to the sacral endplate, the PI has been studied extensively for its association with spinal pathology and used for surgical planning (Faundez and Le Huec, ; Rothenfluh et al, ; Pesenti et al, ). Many have described normative values for PI and subsequently related the normal spinal curvature, including lumbar lordosis and thoracic kyphosis, back to the PI allowing surgical planning to restore spinopelvic harmony (Hasegawa et al, ; Le Huec and Hasegawa, ; Yukawa et al, ). The importance of maintenance or restoration of spinopelvic balance cannot be understated with numerous works demonstrating the correlation of quality of life measures with spinal parameters (Schwab et al, ; Takemoto et al, ; Kyrola et al, ; Protopsaltis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…SVA can be used to determine the relationship between the spine and pelvis, and has a normal range. Yukawa et al [26] reported the average value of 3.1 ± 12.6 mm for the SVA of 626 asymptomatic volunteers, and SVA may steadily increase from ages of 30 to 70 years.…”
Section: Discussionmentioning
confidence: 99%